State Bodies’ Image: Potential of Information and Communication Technologies - Larisa Mikhailovna Belenkova (Управленческое консультирование)
The article substantiates the significance of using information and communication technologies to increase efficiency of state bodies ’ image management . Modern information and communication technologies available to state bodies for positive image-making are conditionally divided into «traditional» and «new» ones. Their qualitative image potential is analyzed. The author suggests practical recommendations on how to improve image support of state bodies’ activities in the Internet.